The impact of technology on the criminal justice system: a psychological overview - Pica, Emily; Ross, David F.; Pozzulo, Joanna (Routledge, Taylor & Francis Group, 2024)
"This comprehensive volume explores the impact of emerging technologies designed to fight crime and terrorism. It is valuable reading for advanced students in Forensic or Legal Psychology and for practitioners, researchers, and scholars in law, criminal justice, and criminology"--